Biologically Modified Polyether Ether Ketone as Dental Implant Material - Ma, Zhangyu; Zhao, Xingyu; Zhao, Jing; Zhao, Zhilong; Wang, Qihui; Zhang, Congxiao (Frontiers in Bioengineering and Biotechnology, 2020)
Polyether ether ketone (PEEK) is a nontoxic polymer with elastic modulus close to human bone. Compared with metal implants, PEEK has advantages such as evasion of stress shielding effect, easy processing, and similar color as teeth, among others. Therefore, it is an excellent substitute material for titanium dental orthopedic implants. However, PEEK's biological inertia limits its use as an implant. To change PEEK's biological inertia and increase its binding ability with bone tissue as an implant, researchers have explored a number of modification methods to enhance PEEK's biological activities such as cellular compatibility, osteogenic activity, and antibacterial activity. This review summarizes current biological activity modification methods for PEEK, including surface modification and blending modification, and analyzes the advantages and disadvantages of each modification method. We believe that modified PEEK will be a promising dental and orthopedic implant material.